Obstructive Sleep Apnea (OSA) Sebagai Faktor Resiko Hipertensi - Sharlene Sabrina Azzahra (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Obstructive Sleep Apnea (OSA) is a common condition where characterized by repetitive upper airway tract obstruction. OSA also characterized by morning sleepiness, frequent awakening during sleep, reduced concentration, and impaired memory. This upper airway tract obstruction could be partial(hypopnea) or complete(apnea). This condition can occur because of several factors, such as heredity, congenital factors like an anatomical abnormality, age, sex, or bodyweight, and also other medical conditions. OSA contributes to the development of cardiovascular diseases, like hypertension. Hypertension is a disorder of the blood vessels that can be defined by ≥140 mmHg systolic blood pressure and/or ≥90 mmHg diastolic blood pressure. Generally, hypertension caused by OSA starts from a hypoxemia condition that turns into systemical inflammation and oxidative stress, endothelial dysfunction, sympathetic nerve, and renin-angiotensin-aldosterone system activation, and sleep deprivation that stimulates peripheral blood vessels constriction, heart rate increase, and arterial blood vessels stiffness.